Examining the Impact of E-Government Development Index (EGDI) and Worldwide Governance Indicators (WGI): A Comparative Study of Thailand and The Six Selected ASEAN Countries - Nur, Utami; Nurmandi, Achmad (Politika: Jurnal Ilmu Politik, 2024)
The purpose of this research is to analyze how the comparison between Thailand and the six selected ASEAN countries in this study, namely Singapore, Brunei Darussalam, Malaysia, Thailand, Indonesia, and the Philippines. This study will analyze the data further using Google Data Studio which is correlated between two indicators, namely the World Governance Indicator (WGI) and the E-Government Development Index (EGDI). Based on the six indicators of the World Governance Indicator (WGI), it can be concluded that on the Voice and Accountability indicator, Thailand scored 82.53 because the freedom of expression in Thailand is still not completely free. On the indicator of Political Stability and Absence of Violence/Terrorism Thailand itself experienced several acts of terror in its country. In the Government Effectiveness indicator, Thailand's Government has implemented good regulatory practices and is committed to improving the quality of regulations. On the Regulatory Quality indicator, Thailand has been working to accelerate reforms for three years to set a solid foundation for sustainable regulatory policy intervention.